Studies on electroless nickel boride coating on boron carbide particles. (October 2014) - Deepa, J. P.; Rajan, T. P. D.; Pavithran, C.; Pai, B. C.
<x content-type="archive" xml:space="preserve">Abstract</x> Ni–B alloy deposits were successfully formed over alkali surface treated boron carbide by electroless technique and the effects of processing parameters such as reduction bath pH, temperature and post-heat treatment were investigated. Microstructural studies show remarkable changes in structural morphology from mesh-like structure to platelet type Ni–B coating. The main Ni–B phases observed were NiB, Ni2B, Ni3B and Ni4B3. An effective Ni–B alloy coating with better surface characteristics was formed at pH 8 under 75°C reaction bath temperature in the presence of bath stabiliser. The post-heat treatment of Ni–B coated particles under varying bath reaction temperatures at 400°C showed remarkable Ni–B phase transformation from metastable NiB and Ni2B to stable crystalline Ni3B phase. The NiB coated particle shows lower particle–matrix interfacial reaction, better wettability and enhanced dispersion in aluminium composites compared to uncoated particles.